THE IMPACT OF THE CORONAVIRUS (COVID-19) PANDEMIC ON INVESTORS’ BEHAVIOUR IN THE LIGHT OF BEHAVIOURAL FINANCE - Marta Wiśniewska (Polityki Europejskie, Finanse i Marketing, 2020)
The aim of the research was to find out the opinions of stockbrokers working at the WarsawStock Exchange regarding the behaviour of Polish investors in the face of the coronavirus(COVID-19) pandemic. The research was carried out among 51 stockbrokers representingbrokerage houses with a long history of operations. It has been found that psychologicalconditions of people and stock market sentiments play an important role in the decision-makingprocess, and irrational investor behaviours, including largely herd effects, are particularly evidentduring the pandemic. The research shows that the occurrence of the coronavirus has not reducedthe activity of Polish investors. Thus, significantly growing interest in shares of companies listedon the Warsaw Stock Exchange has been noted. The behaviour and attitude of market participantstowards risk were volatile during the developing pandemic, which manifested itself in rapid buyingof overvalued assets or rapid selling of assets.